Independent directors : SOX regulations focused new attention on independent advice for boards - Rosenthal, Jean W., 1945- (SAGE knowledge. Cases., 2016)
A series of corporate scandals in 2001 and 2002 led to the collapse of some of the largest U.S. corporations, most spectacularly Enron, Tyco, Global Crossing, and WorldCom, and one 'Big Five' accounting firm, Arthur Andersen. The legislative and regulatory response to these scandals was wide ranging. After hearings and debate, the Congress passed the Sarbanes-Oxley Act of 2002 (abbreviated here as SOX), the Securities and Exchange Commission (SEC) implemented new rules, and U.S. stock exchanges revised their requirements for listing corporations. Designed primarily to stem abuses in financial reporting, these reforms attempted to codify corporate governance rules to protect the interests of investors and make spectacular failures less likely. This case study examines this topic.